DECISION SUPPORT SYSTEM OF GRANTING LOAN AT COOPERATIVE KELUARGA BESAR MUSTAIN USING TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) - Afif Buchori, Muchamad (Institut Teknologi Nasional Malang, 2018)
Mustain Cooperatives is a cooperative engaged in credit business that provides loans or credit. As with most cooperatives, loans or credits that are provided have terms, rules and regulations that aim to provide responsibility to customers or loan applicants in order to keep paying installments every month until the time period agreed by the cooperative and the applicant. Loans made by the cooperative is a decision that greatly affects the development of the cooperative. To get accurate in determining the decision of lending conducted research by applying decision support system using Technique for Order Preference by Similarity to Ideal Solution (TOPSIS).Techniqu for Order Preference by Similarity to Ideal Solution (TOPSIS) is a method of decision support systems whose way of working is to compare alternatives by equating the equality of positive ideal solutions and negative ideal solutions. Selection of the method is due to the method of the fundamental decision support system (SPK) that is so easy to be studied and applied to the making of the program.The results of testing the accuracy of the method both through the simulation program and calculations using Microsoft Excel application states that the calculation results have the difference in the average value range is 0.00130755. The results of functional testing system with access as an admin running according to function in the browser.